2000
DOI: 10.1128/aac.44.4.873-878.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Phenotypic Assay for Detection of Acyclovir-Resistant Varicella-Zoster Virus with Mutations in the Thymidine Kinase Open Reading Frame

Abstract: Susceptibility assays by cell culture methods are time-consuming and are particularly difficult to perform with varicella-zoster virus (VZV). To overcome this limitation, we have adapted a functional test of the viral thymidine kinase (TK) in TK-deficient (tdk mutant) bacteria to detect ACV-resistant VZV in clinical samples. After PCR amplification, the complete viral TK open reading frame (ORF) is purified from PCR primers, digested with two restriction enzymes, and ligated in an oriented fashion into a bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For VZV, a trustworthy alternative strategy for the evaluation of the contribution of VZV TK mutations in antiviral resistance is to assess the in vitro enzymatic activity of mutant TKs. To date, few methods to study in vitro functional activity of VZV TK have been reported: radioactive assays (Ng et al, 2001;Suzutani et al, 2000) and a bacterial colony reduction assay based on restoration of TK-deficient bacteria sensitivity producing functional VZV TK (Sahli et al, 2000). Regarding the herpes simplex virus (HSV), a virus also belonging to the Alphaherpesvirinae subfamily, many methods, either radioactive or non-radioactive ones, have been described for the evaluation of TK phosphorylation activity: radioactive assays based on the use of 3 H-labeled thymidine as a substrate or non-radioactive assays indirectly measuring HSV TK activity (Burrel et al, 2012;Frobert et al, 2007Frobert et al, , 2005Malartre et al, 2012;Sauerbrei et al, 2013;Suzutani et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For VZV, a trustworthy alternative strategy for the evaluation of the contribution of VZV TK mutations in antiviral resistance is to assess the in vitro enzymatic activity of mutant TKs. To date, few methods to study in vitro functional activity of VZV TK have been reported: radioactive assays (Ng et al, 2001;Suzutani et al, 2000) and a bacterial colony reduction assay based on restoration of TK-deficient bacteria sensitivity producing functional VZV TK (Sahli et al, 2000). Regarding the herpes simplex virus (HSV), a virus also belonging to the Alphaherpesvirinae subfamily, many methods, either radioactive or non-radioactive ones, have been described for the evaluation of TK phosphorylation activity: radioactive assays based on the use of 3 H-labeled thymidine as a substrate or non-radioactive assays indirectly measuring HSV TK activity (Burrel et al, 2012;Frobert et al, 2007Frobert et al, , 2005Malartre et al, 2012;Sauerbrei et al, 2013;Suzutani et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of this heterologous system will greatly simplify the identification of mutational hot spots in the TK gene associated with resistance to nucleoside analogues. Moreover, a similar strategy can be used to evaluate the activity of the TK enzyme or its analogue in other herpesviridae (for example varicella-zoster virus [40]) and the impact of TK mutations detected in such viruses.…”
Section: Discussionmentioning
confidence: 99%
“…2001). Unlike HSV, VZV is highly cell‐associated, very labile and replicates slowly in cell culture (Sahli et al. 2000).…”
Section: Discussionmentioning
confidence: 99%